Long-term record of Barents Sea Ice Sheet advance to the shelf edge from a 140, 000 year record. (15th October 2016) - Pope, Ed L.; Talling, Peter J.; Hunt, James E.; Dowdeswell, Julian A.; Allin, Joshua R.; Cartigny, Matthieu J.B.; Long, David; Mozzato, Alessandro; Stanford, Jennifer D.; Tappin, David R.; Watts, Millie
Abstract: The full-glacial extent and deglacial behaviour of marine-based ice sheets, such as the Barents Sea Ice Sheet, is well documented since the Last Glacial Maximum about 20, 000 years ago. However, reworking of older sea-floor sediments and landforms during repeated Quaternary advances across the shelf typically obscures their longer-term behaviour, which hampers our understanding. Here, we provide the first detailed long-term record of Barents Sea Ice Sheet advances, using the timing of debris-flows on the Bear Island Trough-Mouth Fan. Ice advanced to the shelf edge during four distinct periods over the last 140, 000 years. By far the largest sediment volumes were delivered during the oldest advance more than 128, 000 years ago. Later advances occurred from 68, 000 to 60, 000, 39, 400 to 36, 000 and 26, 000 to 20, 900 years before present. The debris-flows indicate that the dynamics of the Saalian and the Weichselian Barents Sea Ice Sheet were very different. The repeated ice advance and retreat cycles during the Weichselian were shorter lived than those seen in the Saalian. Sediment composition shows the configuration of the ice sheet was also different between the two glacial periods, implying that the ice feeding the Bear Island Ice stream came predominantly from Scandinavia during the Saalian, whilst it drained more ice from east of Svalbard during the Weichselian. Highlights: New Barents Sea Ice Sheet history for last 140, 000 years is reconstructed. Glacigenic-debris flows are used to reconstruct ice-sheet history. Four advances to the shelf edge of the Bjørnøyrenna Trough are reconstructed. Weichselian and Saalian Barents Sea Ice Sheets had different configurations. Saalian ice-sheet was stable at the shelf edge longer than any Weichselian ice-sheet.